2013
DOI: 10.1088/0953-2048/26/4/045015
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption study of pinning regimes in Ba(Fe1−xCox)2As2 single crystals

Abstract: Magnetic field dependent modulated microwave absorption (MMWA) measurements have been carried out to investigate vortex pinning effects in single crystals of the iron-based high-Tc superconductor Ba(Fe1−xCox)2As2 with three different cobalt doping levels of x = 0.07, 0.09, and 0.11. The dependence of the MMWA hysteresis loops on temperature, magnetic field, and Co-concentration have been measured and analyzed using a theoretical model of microwave absorption in superconductors. The analysis reveals that in an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Therefore, NRMA studies in iron pnictide superconductors are important. So far, high field sweep magnetically modulated microwave absorption (MMMA) studies have been reported in iron pnictide superconductors [12, 36,37], but at low field sweep, the microwave absorption is unclear. Here, we report a systematic study of low field sweep NRMA on SmFeAsO 0.88 F 0.12 polycrystalline as a function of temperature and field modulation amplitude.…”
mentioning
confidence: 99%
“…Therefore, NRMA studies in iron pnictide superconductors are important. So far, high field sweep magnetically modulated microwave absorption (MMMA) studies have been reported in iron pnictide superconductors [12, 36,37], but at low field sweep, the microwave absorption is unclear. Here, we report a systematic study of low field sweep NRMA on SmFeAsO 0.88 F 0.12 polycrystalline as a function of temperature and field modulation amplitude.…”
mentioning
confidence: 99%